2016
DOI: 10.1016/j.fuproc.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for hemicelluloses extraction from Eucalyptus globulus wood: hydrothermal treatment in a semi-continuous reactor

Abstract: Optimal conditions for hemicellulose extraction from wooden biomass in a semi-continuous system have been assessed in this work. This study would constitute the first stage for a profitable and green industrial process. Eucalyptus globulus was selected as raw material due to its low water consumption, high growth and its efficiency in lignocellulose production. Moreover its cultivation is very popular in southern Europe. Samples of 5.0 g of wood were fractioned using a pressurized hot water semicontinuous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Previous autohydrolysis research was mostly carried out in batch and flow‐through reactors. Examples of dissolution kinetics obtained for hardwood batch autohydrolysis studies have been performed by Garrote et al, Jacobsen and Wyman, Mittal et al, Tunc and van Heiningen, and Borrega et al Similar through‐flow studies are shown by Kilpelainen et al, Borrega and Sixta, and Gallina et al However, batch reactors are not best suited to study the intrinsic dissolution kinetics of the different wood components because they degrade further in the bulk of the solution. This problem is overcome in a tubular flow‐through reactor when the liquid residence time is relatively short so that the dissolved components are quickly removed from the high temperature system.…”
Section: Introductionmentioning
confidence: 88%
“…Previous autohydrolysis research was mostly carried out in batch and flow‐through reactors. Examples of dissolution kinetics obtained for hardwood batch autohydrolysis studies have been performed by Garrote et al, Jacobsen and Wyman, Mittal et al, Tunc and van Heiningen, and Borrega et al Similar through‐flow studies are shown by Kilpelainen et al, Borrega and Sixta, and Gallina et al However, batch reactors are not best suited to study the intrinsic dissolution kinetics of the different wood components because they degrade further in the bulk of the solution. This problem is overcome in a tubular flow‐through reactor when the liquid residence time is relatively short so that the dissolved components are quickly removed from the high temperature system.…”
Section: Introductionmentioning
confidence: 88%
“…[c] corn stover0.465 [148] 0.337 [149] 0.2050.228 0.087 0.143 12.61 [150] 25 cotton straw 0.498 [88] 0.426 [88] 0.2710 .182 0.041 0.080 15.62 [150] 25 EFB 0.455 [151] 0.383 [143] 0.3530 .221 0.016 0.027 14.54 [85] 25 energy cane bagasse 0.467 [151] 0.433 [152] 0.2380 .217 0.008 0.104 10.01 [153] 50 eucalyptus wood 0.529 [154] 0.425 [155] 0.2290 .275 0.002 0.069 12.56 [156] 25 giant reed 0.471 [157] 0.311 [158] 0.3530 .185 0.061 0.090 12.52 [159] 25 giant miscanthus0.484 [160] 0.504 [161] 0.2480 .120 0.027 0.101 12.46 [162] 25 oat hulls 0.460 [154] 0.363 [163] 0.3850 .058 0.054 0.140 12.14 [164] 25 OPF 0.480 [160] 0.304 [143] 0.4040 .217 0.058 0.017 11.12 [165] 25 paper sludge0.490 [166] 0.491 [167] 0.1710 .194 0.102 0.042 7.479 [160] 50 pinewood 0.494 [154] 0.537 [168] 0.0640 .324 0.029 0.046 12.77 [169] 25 rapeseed residue 0.445 [170] 0.440 [171] 0.1780 .192 0.130 0.060 10.01 [160] 50 rice husks 0.388 [157] 0.310 [172] 0.2430 .143 0.217 0.087 12.75 [173] 25 rice straw 0.382 [157] 0.342 [174] 0.2130 .267 0.115 0.063 13.84…”
Section: Biomassmentioning
confidence: 99%
“…As a whole, it can be observed that grape stems seemed to have a completely different behaviour if compared with other woody biomasses since higher sugars yield were expected at a temperature of 180ºC (Cocero et al, 2018a). Nevertheless, the extraction yield respect to the biomass able to be recovered was similar to the reported by other authors in literature (67 vs 60%, respectively) (Gallina, Cabeza, Biasi, & García-Serna, 2016;Yedro et al, 2017).…”
Section: Oligomers Sugars and Degradation Productssupporting
confidence: 83%